Citizenship survey, 2008-2009 (Citizenship survey, 2010)
The Citizenship Survey (known in the field as the Communities Study) ran from 2001 to 2010-2011. It began as the 'Home Office Citizenship Survey' (HOCS) before the responsibility moved to the new Communities and Local Government department (DCLG) in May 2006. The survey provided an evidence base for the work of DCLG, principally on the issues of community cohesion, civic engagement, race and faith, and volunteering. The survey was used extensively for developing policy and for performance measurement. It was also used more widely, by other government departments and external stakeholders to help inform their work around the issues covered in the survey. The survey was conducted on a biennial basis in 2001, 2003, 2005 and 2007-2008. It moved to a continuous design in 2007 which means that data became available on a quarterly basis from April 2007. Quarter one data were collected between April and June; quarter two between July and September; quarter three between October and December and quarter four between January and March. Once collection for the four quarters was completed, a full aggregated dataset was made available, and the larger sample size allowed more detailed analysis. In January 2011, the DCLG announced that the Citizenship Survey was to close. As part of the drive to deliver cost savings across government and to reduce the fiscal deficit, research budgets were closely scrutinised to identify where savings can be made. For this reason, and the belief that priority data from this survey could either be dropped; collected less frequently; or collected via other means, the survey was cancelled. Fieldwork concluded on 31 March 2011, followed by publication of reports in the months after analysis of that data. Further information about the survey, including links to publications, can be found on the National Archives webarchive page for the Citizenship Survey. The Consultation outcome: the future of the citizenship survey statement can be viewed on the gov.uk website. The Community Life Survey, (held under GN 33475), which began in 2012-2013 and is conducted by the Cabinet Office, incorporates a small number of priority measures from the Citizenship Survey, in order that trends in these issues can continue to be tracked over time. For these measures the Community Life Survey findings are comparable to the Citizenship Survey findings.